The taste and smell in the perception of the diner of a restaurant in Lima, August 2022 - Ana S. Córdova (2025)
The objective of this study was to determine the influence of taste and smell on diners’ perception in a restaurant in Lima, focusing on two emblematic dishes of Peruvian gastronomy: arroz con pato (rice with duck) and hot ceviche. The research was conducted under a quantitative approach, with a correlational and cross-sectional design. The sample consisted of 378 diners from Fiesta Restaurant, selected using a finite population formula with a 95 % confidence level. Data were collected through a structured eight-question digital questionnaire, and results were analyzed using descriptive and inferential statistics. Findings indicate that 97 % of respondents considered aroma an important factor during dish tasting, while 100 % identified taste as a decisive element in their dining experience. Additionally, 66 % reported a very high level of perception related to taste, and 52% expressed a high perception regarding aroma. These results confirm that taste and smell are closely linked in shaping gastronomic experiences, reinforcing the theoretical contributions of neurogastronomy and gastrophysics. The study provides empirical evidence in the Peruvian context, highlighting the relevance of sensory dimensions in culinary evaluation and suggesting that restaurants may design multisensory strategies to enhance customer satisfaction and strengthen gastronomic innovation.